'Stay at home …': exploring the impact of the COVID-19 public health response on sexual behaviour and health service use among men who have sex with men: findings from a large online survey in the UK. (20th September 2021) - Howarth, Alison R; Saunders, John; Reid, David; Kelly, Isabelle; Wayal, Sonali; Weatherburn, Peter; Hughes, Gwenda; Mercer, Catherine H
Abstract : Objectives: The first UK national lockdown began on 23 March 2020, in response to the COVID-19 pandemic, and led to reduced STI/HIV service provision in the UK. We investigated sexual behaviour, use and need for sexual healthcare during the pandemic. Methods: Participants (N=2018), including men (cis/transgender), transwomen and gender-diverse people reporting sex with another man (cis/transgender) or non-binary person assigned male at birth, completed an online cross-sectional survey (23 June 2020–14 July 2020), in response to adverts on social media and dating apps. Sexual behaviour, service use and unmet need for STI testing (any new male and/or multiple condomless anal sex (CAS) partners without STI testing) in the 3 months since lockdown began were examined and compared using multivariable analyses with an equivalent 3-month period in a 2017 survey (N=1918), conducted by the same research team. Results: Since lockdown began, 36.7% of participants reported one or more new partners, 17.3% reported CAS with multiple partners, 29.7% HIV testing (among 1815 of unknown/negative status), 24.9% STI testing and 15.4% using pre-exposure prophylaxis (PrEP). Since lockdown began, 25.3% of participants had unmet need for STI testing. This was more likely among Asian versus white participants (adjusted OR (aOR)=1.76, (1.14 to 2.72), p=0.01); for participants living in Scotland (aOR=2.02, (1.40 to 2.91), p<0.001) or Northern Ireland (aOR=1.93, (1.02–3.63), p=0.04) versus England; and for those living with HIV (aOR=1.83, (1.32 to 2.53), p<0.001). Compared to 2017, the equivalent 2020 subsample were less likely to report new male partners (46.8% vs 71.1%, p<0.001), multiple CAS partners (20.3% vs 30.8%, p<0.001) and have unmet need for STI testing (32.8% vs 42.5%, p<0.001) in the past 3 months. Conclusions: We found potential for ongoing STI/HIV transmission among men who have sex with men during the initial UK lockdown, despite reduced sexual activity, and inequalities in service access. These findings will support public health planning to mitigate health risks during and after the COVID-19 response.